GAMBARAN IKLIM ORGANISASI SEBAGAI DASAR PENGEMBANGAN ORGANISASI - Gracia Tobing; Rayini Dahesihsari; Benedicta P. Dwi Riyanti; Nani Indra Ratnawati Nurrachman (MANASA, 2015)
The important impact of how employees perceived their working environment, practices, policies, values, and interaction in organization affecting their working experiences on their working behavior has been well known in the field of organizational psychology. Poor vertical and horizontal relationship, the mismatch policies and goals, lack of motivation, and work productivity are the examples of problems that may be arise if organizational climate were not well managed. Full attention to organizational climate has been the inevitable demand for organizations that are in a situation with strict competition. This research aimed to get a comprehensive description of organizational climate, based on Competing Value Model theory that were presented by Patterson, West, Shackleton, Jeremy, Lawthom, Maitlis, Robinson, dan Walace. The description will be used for guiding how the management develop their organization. A combination of quantitative and quality approaches was implemented by using quetionnaires and interviews. The participants are 59 employees with minimum supervisory level as the criteria. Descriptive statistic and anova one-way were used for analyzing quantitive data. Content analysis with inductive analysis was used for analyzing qualitative data. The result showed that more attention was needed for organizational climate, especially on internal process, human relation, and rational goal. Those aspects will be the focus to develop for management.